Measurement of the amplitude pattern and the frequency characteristic of ISM-band antennas using WiFi routers - А. В. Садченко; O. A. Кушниренко; И. В. Цевух; И. А. Валянский; Ю. С. Чихрай (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The quality of a wireless network depends essentially on the directional characteristics of the antennas, the most important of which are the amplitude radiation pattern (RP) and the frequency response (FR), which is understood as a change of the gain coefficient in the working frequency band. At the same time, equipment for measuring the characteristics of the antennas in real conditions is very expensive, difficult to deploy, configure and maintain. In most cases, the measurement accuracy requirements are significantly lower than in laboratory measurements. This fact allows using the equipment which is part of the wireless network itself. The aim of this work is to develop a simplified procedure for measuring the amplitude RP and frequency characteristics of antennas for the rapid assessment of electromagnetic environment during deployment of wireless networks, when the requirements for measurement accuracy are not critical. In this article we propose to use as a UHF calibrated power generator a standard Wi-Fi router with a coaxial output, i.e. with the possibility to connect an external antenna. Certified routers 802.11n standard of 2.4 GHz band, regardless of the manufacturer, provide the following parameters: output power range of 20–100 mW, receiver sensitivity of 80–85 dBm, dynamic range of the receiver — 90 dBm. Using system settings of the router allows one to rapidly change the frequency in the range of 2400–2483.5 MHz with a step of 5–20 MHz. The practical value of the proposed methodology for measuring Wi-Fi antennas characteristics consists in substantial saving of time and costs during deployment and adjusting of wireless networks. This method can be successfully used for testing city wireless video surveillance systems and public access points to the local and global resources of city network.